PENEGAKAN HUKUM DALAM UPAYA PENANGGULANGAN PROSTITUSI DI KOTA SEMARANG - Pujiyono, Henny Juliani, Devananda Wahyu Kusumawardhana, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Prostitution becomes a problem in Semarang city. There is lots of pro contra that occurred due to the existence of prostitution being a complicated and difficult to solve. Need a clear policy on prostitution, especially to eliminate women and girls trafficking for sexual exploitation purpose. The approach method that is used in this research is a normative-empirical approach. Approach to this research and writing begins by explaining and describing the phenomena and then analyzed both normatively and socially. The population that was appointed to be representative samples: the chief of prostitution prevention institutions, the public figures around the prostitution area, and the commercial sex workers that caught on sweeping. Prostitution tackling is done by 4 elements: 1) Public Health Service, by an appeal to public either in the form of socialization and provide counseling and also conduct programs that aimed to sex workers by holding special clinics to perform a series of events that lead to physical and health factors, 2) Department of Social Welfare, the efforts to tackle a prostitution by giving coaching and training skills in order to the sex workers have provision to face the life feasibility and can detached from prostitution life, 3) Police, with intensively conducted Cipta Kamtibmas Operation with a code â€œOperasi Pekatâ€ or society diseases includes alcohol, gambling, prostitution and thuggery, 4) Civil Service Police Unit that was an agencies of Semarang City Government who active in tackling the prostitution problem in Semarang city in accordance to the Regulation No. 10 of 1965 about Bank Street Prostitution and about Closing of Prostitution Houses Place. Prostitution tackling should be established to maintain a public tranquility and maintenance the society peace. Prostitute is acts that cause many troubles such as safety, orderliness, and even lead to society diseases.